Agronomic and hormonal approaches for enhancing flowering intensity in white Guinea yam (Dioscorea rotundata Poir.) - Mondo, Jean M.; Agre, Paterne A.; Chuma, Géant B.; Asiedu, Robert; Akoroda, Malachy O.; Asfaw, Asrat (Frontiers in Plant Science, 2023)
Developing novel white Guinea yam (Dioscorea rotundata) varieties is constrained by the sparse, erratic, and irregular flowering behavior of most genotypes. We tested the effectiveness of nine agronomic and hormonal treatments to enhance flowering on D. rotundata under field conditions.Genotypes responded differently to flower-inducing treatments (p<0.001). Of the test treatments, pruning and silver thiosulfate (STS) were effective in increasing the number of spikes per plant and the flowering intensity on both sparse flowering and monoecious cultivars. STS and tuber removal treatments promoted female flowers on the monoecious variety while pruning and most treatments involving pruning favored male flowers. None of the treatments induced flowering on Danacha, a non-flowering yam landrace. Flower-enhancing treatments had no significant effect on flower fertility translated by the fruit set, since most treatments recorded fruit sets above the species' average crossability rate. Flower-enhancing techniques significantly influenced number of tubers per plant (p = 0.024) and tuber dry matter content (DMC, p = 0.0018) but did not significantly affect plant tuber yield. Nevertheless, treatments that could enhance substantially flowering intensity, such as pruning and STS, reduced tuber yield. DMC had negative associations with all flowering-related traits. This study provided insights into white yam flower induction and suggests promising treatments that can be optimized and used routinely to increase flowering in yam crop, without significantly affecting flower fertility and tuber yield.